Depositionally-Induced Magnetic Frequency Variations of a Sandstone Facies from the Copper Harbor Conglomerate of the North American, Mid-Continent Rift at Union Bay, Michigan - Borucki, Elizabeth Anne (Proceedings of the Wisconsin Space Conference, 2019)
Precambrian sandstones were investigated to determine whether deep-time, fluvial red-beds can maintain magnetic variations related to deposition. Using an easily accessible site on Earth, it is possible to define methods that benefit future studies related to magnetic variations as linked to conditions of formation. The study utilized environmental magnetism and cyclostratigraphic techniques to determine magnetic characteristics and susceptibility variation frequencies. Magnetite and hematite were inferred from laboratory measurements and the magnetic fabric agreed with previous paleocurrent observations, suggestive that susceptibility correlates with deposition. Hematite concentration controlled susceptibility: high-susceptibility corresponded with large grain-sizes and cross-bedding, while low-susceptibility was attributed to small grain-sizes and erosional or color boundaries. A statistically-significant, cyclic, susceptibility signal was observed from the stratigraphy, suggesting that susceptibility variations may arise from climatically-induced variations in depositional or post-depositional processes. The observed frequency also supports the capacity for fluvial red-bed deposits to maintain depositional characteristics original to formational processes.